2011
DOI: 10.1073/pnas.1100758108
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of filaments formed by human Xrcc4–Cernunnos/XLF complex involved in nonhomologous DNA end-joining

Abstract: Cernunnos/XLF is a core protein of the nonhomologous DNA end-joining (NHEJ) pathway that processes the majority of DNA double-strand breaks in mammals. Cernunnos stimulates the final ligation step catalyzed by the complex between DNA ligase IV and Xrcc4 (X4). Here we present the crystal structure of the X4 1-157 -Cernunnos 1-224 complex at 5.5-Å resolution and identify the relative positions of the two factors and their binding sites. The X-ray structure reveals a filament arrangement for X4 1-157 and Cernunno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
131
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(140 citation statements)
references
References 38 publications
9
131
0
Order By: Relevance
“…previous reports that XLF/XRCC4 can form filaments in the absence of DNA (41). When the proteins Ku, LX, and XLF were reacted, we observed similar filaments when staining for LigIV ( Fig.…”
Section: Sr Imagingsupporting
confidence: 82%
See 2 more Smart Citations
“…previous reports that XLF/XRCC4 can form filaments in the absence of DNA (41). When the proteins Ku, LX, and XLF were reacted, we observed similar filaments when staining for LigIV ( Fig.…”
Section: Sr Imagingsupporting
confidence: 82%
“…have shown that XLF and XRCC4 form extended filaments (26,27,(38)(39)(40)(41)(42). Importantly, our SR imaging revealed that XRCC4 and XLF filaments exist in vivo, and also that LigIV appears to form filamentous structures in cells (Fig.…”
Section: Sr Imagingsupporting
confidence: 52%
See 1 more Smart Citation
“…Accordingly, Cernu Ϫ/Ϫ mice crossed onto the P53 KO background did not develop B cell lymphoma, as opposed to the case with other NHEJ deficiency situations (26). We propose a speculative yet plausible explanation for this intriguing observation, based on our recent report on the Cernunnos-Xrcc4 complex structure (27). Crystals of Cernunnos-Xrcc4 complexes revealed that both homodimers associate with each other in long filaments through their head domains, helping to tether the broken DNA ends by creating a "DNA ligation synapse" (27)(28)(29)(30).…”
Section: Discussionmentioning
confidence: 60%
“…Since its discovery in 2005, several functions have been described for XLF. It stimulates LIG4 activity, 21,22 and it can form long filaments with XRCC4 that keep the DNA ends together in a ligation synapse, 24,[48][49][50][51] and XLF is essential for gap-filling by polymerase (pol) l and polm during NHEJ. The latter function is interesting, as poll and polm belong to the same polX family of polymerases as For personal use only.…”
Section: Discussionmentioning
confidence: 99%